Computer – Aided RGB analyses of images - Alizoti, Alion (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Computers have long been applied to physics and education. Considering that computer technologies are affecting science in many ways, special attention is payed to images and image analyses. RGB processing is used to analyse several computer images and presented with this papper. Furthermore, numerical data from images are used to tables and graphs, to motivate students devoted to science and research.